The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3389/fpubh.2023.1145486
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction with pediatric telehealth according to the opinions of children and adolescents during the COVID-19 pandemic: A literature review

Abstract: ObjectiveTo review satisfaction with telehealth among children and adolescents based on their own opinions during the COVID-19 pandemic.MethodsIn the PubMed, CINAHL, PsycINFO, and Embase databases, we searched for peer-reviewed studies in English on satisfaction with telehealth among children and adolescents (rather than parents). Both observational studies and interventions were eligible. The review was categorized as a mini review because it focused on the limited time frame of the COVID-19 pandemic. We foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…PSWs also reported challenges in referring parents to a family intervention which would necessitate missing work. School settingsin which parents may face barriers to attending school clinics-may not be ideal for this particular family-based intervention, however, given the recent advances in the availability of telehealth during the COVID-19 pandemic (e.g., Kodjebacheva et al, 2023), involving families in remote care that is initiated through schools is an area for (Mogil et al, 2022). Future studies would also benefit from a mixed methods approach with both quantitative and qualitative feedback from providers, students, and caregivers, to provide a contextual understanding of implementing the intervention among youth and families.…”
Section: Discussionmentioning
confidence: 99%
“…PSWs also reported challenges in referring parents to a family intervention which would necessitate missing work. School settingsin which parents may face barriers to attending school clinics-may not be ideal for this particular family-based intervention, however, given the recent advances in the availability of telehealth during the COVID-19 pandemic (e.g., Kodjebacheva et al, 2023), involving families in remote care that is initiated through schools is an area for (Mogil et al, 2022). Future studies would also benefit from a mixed methods approach with both quantitative and qualitative feedback from providers, students, and caregivers, to provide a contextual understanding of implementing the intervention among youth and families.…”
Section: Discussionmentioning
confidence: 99%
“…Parents and HCPs were very satisfied with how convenient and easy communication was, but the HCPs reported that the inability to make accurate clinical assessments using the tablet was a significant challenge [38]. Research also shows that another concern is that telemedicine may depersonalize the patient and clinician relationship due to a lack of in-person interaction [11,39]. These key concerns must be taken into consideration when developing an eHealth intervention.…”
Section: Comparison With Prior Workmentioning
confidence: 99%
“…“Among the 14 studies, two were interventions. The participants preferred a mix of in-person visits and telehealth services, but they also showed high satisfaction with video and phone appointments as well as home telemonitoring” ( 2 ). In the health sector, telemedicine technology has evolved as a useful tool that assists patients in a variety of ways ( 3 ).…”
Section: Introductionmentioning
confidence: 99%